PENERAPAN METODE RATIONAL UNIFIED PROCESS PADA KNOWLOEDGE MANAGEMENT SYSTEM UNTUK MENDUKUNG PROSES PEMBELAJARAN SEKOLAH MENEGAH ATAS - Muryan Awaludin; Rinta Ridyustia Raveena (Fakultas Ilmu Komputer dan Desain - Unsurya, 2021)
AbstractUtilization of information technology in schools is necessary to improve the quality of schools and also facilitate every learning, especially teaching and learning activities that occur in high school. Given the large class capacity and limited study space, knowledge management is needed to improve the quality of performance and competence of each individual, both students and teachers. The application of the Rational Unified Process (RUP) method on the Knowloedge Management System to support the high school learning process. Based on the results of tests carried out where the population sample is 963 students in the Bekasi area, the results of respondents show strongly agree 75.6%, it can be concluded that the application of RUP to this knowledge management system can help teachers in the learning process by distributing material, especially in the form of videos. for students to better understand the material that has been presented.Â Keywords: Knowledge Management, RUP, and Learning